(untitled) (Research, Society and Development, 2020)
Introduction: Nonspecific low back pain can be caused by several factors, such as postural changes, ergonomic factors and through biomechanical dysfunctions in the sacroiliac and lumbar joints. Objective: To verify the effects that pelvic steering wheel mobilization brings on the lumbar spine in patients with nonspecific low back pain. Methods: The study is almost experimental before and after, analytical descriptive, cross-sectional and quantitative, composed of 20 women with nonspecific low back pain, aged between 18 and 28 years of age. The study was divided into four stages: the first was through the application of a socio-clinical questionnaire, VAS scale and the low back pain questionnaire, which quantifies the intensity of low back pain. In the second stage, the ascending thumb test was applied, evaluating the position of the iliacs. In the third stage, the mobilization of the pelvic steering wheel type was the interventional method, through three series of 60 repetitions. In the fourth stage, the revaluation was performed. Results: There was a reduction in low back pain found through the VAS scale going from 7,286 ± 1,309 to 1,81± 1,25, the low back pain questionnaire with an initial mean of 2,64 ± 0,44 and the end of 1,96 ± 0,54; regarding the ascending thumb test, there was predominance of right iliac anteriority and after mobilization application there was 85.71% pelvic leveling. Conclusion: The mobilization of the pelvic steering wheel type obtained repercussions regarding the reduction of low back pain and correction of sacroiliac dysfunctions.